Essential Text on Local Government Law in Zambia - Chirwa, J. (Juta & Company, Limited, 2020)
Essential Text on Local Government Law in Zambia is an important book that dissects the concepts and themes surrounding local government in Zambia. The book is a must-have guide for all role-players and stakeholders in local government administration in Zambia. It will be of much use to councillors, local government administrators, public administrators, town clerks, human resources managers and students of law